Exiting their comfort zone: Unpacking the educational experiences of Nigerian students in China - Umennadi, Juliet; Ifekpolugo, Chinelo; Egwuonwu, Matthew Ekene (Journal of International Students, 2025)
The paper highlighted the voices of six Nigerian students who lived and studied in China for a duration of four to seven years, by investigating their educational experiences. We focused on the challenges encountered, coping mechanisms employed and ultimately, their post-China reflection, which was an attempt at understanding the value of their study migration to China. To guide the study, a narrative inquiry approach was employed and six themes emerged: feeling out of place; trying to blend in, teachers’ support, language of instruction, learning to cope, in addition to exiting China-their comfort zone (a post-China reflection). Other findings revealed the alignment between the participants’ Chinese degrees and their present job/career, the value of meaningful connection, amongst others. Furthermore, the paper calls for further investigation on the aspect of mixed-classroom integration and learning experience between international and host students.